Work engagement, well-being, and intent to continue working based on educational support among foreign care workers in Japan - Junko Kameyama; Yumi Hashizume; Yuko Takamura; Shoko Nomura; Tomoki Gomi; Hisako Yanagi (Komiyama Printing Co. Ltd, 2022)
Background: Global aging continues to progress. The shortage of human resources involved in long-term care (LTC) is a serious problem worldwide. It is necessary to promote the stable employment of foreign care workers. The purpose of this study was to identify which factors, including well-being, work engagement, and original items, contribute to foreign care workers' intent to continue working. Methods: We conducted an anonymous self-administered questionnaire survey of 259 foreign LTC workers at LTC facilities in Japan. The questionnaire survey items included the Japanese version of the Subjective Well-being Scale (J-SWBS), the Japanese version of the Utrecht Work Engagement Scale (J-UWES), and original items related to educational needs and issues. We used multiple regression analysis to predict variability from correlations among variables. And after that, we conducted a path analysis using structural equation modeling (SEM), and added that the explanatory variables (IV) were well-being, work engagement, and the original item component, and that the outcome variable (DV) was intention to continue working. We set a hypothetical model based on structural equations, corrected by path analysis, and examined its suitability. Results: The number of returned questionnaires for 259 foreign care workers was 147 (response rate 56.7%), and the number of analyzable questionnaires was 129 (valid response rate 49.8%). For intention to continue working, the results of structural equation modeling showed direct effects for satisfaction with low back pain measure guidance (β = .255), satisfaction with the national examination guidance method (β = .217), well-being (β = .046), and work engagement (β = .026). In work-engagement, there was a direct effect of happiness (β = .715), willingness to learn good care (β = 4.849), and confidence in my ability (β = 2.902,), whilst in well-being, satisfaction with low back pain measure guidance (β = 1.582) and confidence in my ability (β = 1.999) were found to have direct effects. Conclusions: To increase the intent of foreign care workers to continue working, appropriate guidance should be given related to the development of lumbago. In addition, to provide a place and scene where they can learn good care, having a relationship in practice where foreign care workers can feel that their abilities are being utilized, and developing and maintaining educational support that motivates them to learn good care may be effective.